2022
DOI: 10.2147/ca.s347743
|View full text |Cite
|
Sign up to set email alerts
|

Does a Renal Vascular Variation in the Renal Allograft Determine the Outcome of Renal Transplantation? Experience from the National Kidney Transplantation Center, Ethiopia

Abstract: Renal vascular anatomy is known for presenting a wide range of variations. Kidneys with variant renal vascular anatomy, when used as a graft, appear to have a potential risk that could impair the outcome of kidney transplantation. Information on renal vascular variation and its implication in the surgical outcome of renal transplantation has not been well studied. The present study was aimed at evaluating the outcome of transplantation of renal allografts with variant renal vasculature as compared to allograft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This finding supports the reports of Hlaing, et al, [15], Odman and Ranniger [16], Natsis, et al, [17], Santos Soares, et al [18], Sungura [19], Kapoor et al [20] and Oh et al [21]. Differing from the previously mentioned results, this is higher than what were found by Gebremickael A, et al [22], Wondmagegn, et al, [23], Hekimoglu A and Ergun O, [24] Majos M, et al, [25], Salih M A and Hasan MA, [26], Ahmed A Y, et al, [27], Coen & Raftery [28]. In many studies, the sample was dissected cadavers or specimens from an autopsy, while in other angiographic studies, the sample was patients.…”
Section: Discussionmentioning
confidence: 88%
“…This finding supports the reports of Hlaing, et al, [15], Odman and Ranniger [16], Natsis, et al, [17], Santos Soares, et al [18], Sungura [19], Kapoor et al [20] and Oh et al [21]. Differing from the previously mentioned results, this is higher than what were found by Gebremickael A, et al [22], Wondmagegn, et al, [23], Hekimoglu A and Ergun O, [24] Majos M, et al, [25], Salih M A and Hasan MA, [26], Ahmed A Y, et al, [27], Coen & Raftery [28]. In many studies, the sample was dissected cadavers or specimens from an autopsy, while in other angiographic studies, the sample was patients.…”
Section: Discussionmentioning
confidence: 88%
“…However, Wondmagegn, et al, found that there is no significant difference was noted in the overall outcome of transplantation of renal allografts with and without vascular variations. Hence, renal allografts with vascular variations are safe to be recruited for transplantation [17].…”
Section: Discussionmentioning
confidence: 99%